MODEL SISTEM PENGOLAHAN NILAI AKADEMIK BERBASIS WEB DENGAN PENDEKATAN,SER VICE ORIENTED ARCHITECTURE DI SMP NEGERI 2 KEMBARAN - Budhy Susanto (Telematika, 2010)
The developmenl of inforntation technologt allows the e,stablishment o/systems that can meelthe need for inforntation and rapid and accurate progre,ss of student learning. Based on theassumption that the approach to Service Oriented Architecture (SOA) is more suitable to thecharacteristics of a dynamic educational system, lhis research has oims to produce academicvalue model processing system using this approach. Given the web service is animplementation of SOA technologt most commonly used, then selected the lVindowsComntunication Foundation (WCF) in the construction of foundation systems designedlayered (multi-tier). The results showed that the model system can be built, and based on theresults of the testing system is performing relatively well and deserve to be implemented inSMP Negeri 2 Kembaran and other educational unil that canies out the assessment on thebasis of the Minister of National Education Regulation No. 20 of 2007 on the StandardAss essment of Education.